Keunikan Pembelajaran Madrasah Berbasis Pesantren: Studi Kualitatif dalam Konteks Pendidikan Agama Islam - Darojah, Nely Irnik; Zubad, Ahmad; Fatkhullah, Kamal; Khumaedah, Isti; Rohmatika, Maulida; Nurazizah, Laila Riza; Munadhifah, Siti; Khotimah, Khusnul; SYIFA'UDIN, ABDULLAH (LPPM Sekolah Tinggi Islam Kendal, 2025)
Pesantren-based madrasahs have unique characteristics in their learning system, as they integrate formal education with Islamic scholarly traditions rooted in pesantren values. This study aims to explore the uniqueness of learning practices in pesantren-based madrasahs, emphasizing the combination of the national curriculum with pesantren-specific curricula rich in moral, spiritual, and disciplinary values. This research employed a qualitative descriptive approach using observation, interviews, and documentation involving teachers, students (santri), and school administrators. The findings reveal that the uniqueness of learning in pesantren-based madrasahs lies in the integration of general and religious knowledge, daily worship practices, close emotional bonds between teachers and students, and an environment conducive to shaping Islamic character. These findings contribute to the development of an integrative educational model that is relevant to contemporary needs while preserving fundamental Islamic values.